Estudio de factibilidad de un modelo innovador de simbiosis industrial para un proyecto estratégico del sector minero, en la fase de beneficio del mineral en el distrito Zaruma-Portovelo - Logroño Guarderas, Roberto Moisés (2017)
The research project aims to determine a feasibility study of an innovative model of industrial symbiosis for a strategic project of mining sector, as benefit of the mineral in the district of Zaruma-Portovelo. To demonstrate the necessity of applying sustainable strategies for industrial ecology in the phase of benefit of the handmade mining developments in Portovelo - Zaruma, reducing the environmental impact. The absence of sustainability of the economic growth has reached environmental impacts caused by bad handling of dangerous industrial garbage in the mining sector. The application of sustainable strategies of industrial ecology in the phase of benefit of the handmade mining companies in Portovelo-Zaruma will allow reducing the environmental impact, taking into consideration that in this phase the mineral of interest is separated by metallurgical process, with different techniques; physical and chemical procedures. This study will develop with base in the proper concepts and categories of the industrial ecology, taking the Ecuadorian mining sector as an object of specific study, specially the region of Portovelo-Zaruma, where the main interest will be the benefit stage, indicating the importance that has for the same one the application of the special strategies, in order to determine the environmental impact of the mining activities, and to raise measurements faced to mitigate it.